Current role of endoscopic ultrasound for gastrointestinal and abdominal tuberculosis. Issue 11 (30th September 2022) - Maulahela, Hasan; Fauzi, Achmad; Renaldi, Kaka; Srisantoso, Qorina P; Jasmine, Amirah
Abstract: A high incidence of tuberculosis (TB), especially in endemic countries, makes this infectious disease a concern. Abdominal TB contributes to 10% of extrapulmonary TB. Due to nonspecific clinical, radiological, and endoscopic findings, diagnosing abdominal TB continues to be a challenge. Hence, a precise diagnosis is needed. The diagnosis of gastrointestinal disease using endoscopic ultrasound (EUS) is often performed due to its high resolution and ability to provide a real‐time visual representation of the gastrointestinal tract and extramural structures. EUS‐guided fine‐needle aspiration (FNA) and fine‐needle biopsy (FNB) have helped diagnose TB as they offer an adequate specimen for cytology or histopathological examination. This method is considered safer, more effective, and more efficient. The capacity of EUS to diagnose abdominal TB based on the affected organs was examined via a literature search. We reviewed the role of EUS in diagnosing esophageal, gastric, pancreatic, peripancreatic, hepatosplenic, peritoneal, and intestinal TB. Generally, EUS aids in diagnosing abdominal TB. In some organs, it is superior to other diagnostic modalities. However, further examinations, such as cytology or histopathology and microbial, are still needed. We also studied the roles of EUS‐FNA and EUS‐FNB. EUS‐FNA has shown a high diagnostic yield in esophageal (94.3–100%), pancreatic and peripancreatic (76.2%), and intestinal TB (84.1%). As minimally invasive methods, EUS‐FNA and EUS‐FNB can successfully provide sufficient samples. EUS is a functional diagnostic modality for abdominal TB. EUS‐FNA and EUS‐FNB provide sufficient samples safely and efficiently for further cytology, histopathology, and microbial examinations. Abstract : Gastrointestinal and abdominal tuberculosis (TB) manifestations are similar to those of other gastrointestinal diseases. Due to the non‐specific findings, diagnosing them remains a challenge. This article aims to review the role of endoscopic ultrasound (EUS) and EUS‐guided fine‐needle aspiration/fine‐needle biopsy in diagnosing gastrointestinal and abdominal TB so that patients can get appropriate treatment with a minimally invasive diagnostic approach.